Evaluation with stream characteristics of downstream flood problems after dam construction - Bagatur, Tamer; Hamidi, Nizamettin (Journal of Environmental Engineering and Landscape Management, 2014)
The food may cause serious loss of life and property. The evaluation of food events is necessary for the planning and design of engineering projects. In a dam, food problems should be considered for both upstream and downstream conditions. The characteristics of food problems can be derived from observation of dam sites. Tis paper aims to evaluate the impact of food hazards from spillway based on downstream conditions after dam construction. Also, the paper discusses downstream food problems depending on stream characteristics in an example dam site. In results, three reasons are determined for downstream foods problems: control problems of spillway gates, the naturally developing vegetation through channel flow line and incompetence of stream cross-section for carrying of food flows. Therefore, downstream conditions should be investigated before dam construction. Tis investigation can be considered in the planning phase. In addition, the cross-section and longitudinal profile of stream should be controlled via maintenance of stream after dam construction. In stream cross-section problems (such as vegetation, incompetence and irregularities), some modifications (e.g. straighten, deepen, and widen) can be applied with engineering works. First published online: 18 Mar 2014